Sexual and natural selection interplay in sexual head shape dimorphism of two sympatric racerunners (Squamata: Lacertidae) - Liang, Tao; Wang, Li; Shi, Lei (Frontiers in Ecology and Evolution, 2022)
Both natural and sexual selection can shape sexual dimorphism. However, determination of the contribution of these selection pressures is challenging. In lizards, sexual selection can contribute to the larger head size of males than that of females. However, males and females can also diverge in their head size to prey on different food resources under conditions of limited resources (and/or high competitors). Here, 109 individuals from two sympatric desert lizards (Eremias grammica: 28 males and 30 females; E. velox: 25 males and 26 females) were studied to determine their sexual head shape (head length, width, and depth). Additionally, 191 and 169 feces samples of E. grammica and E. velox, respectively, were collected to assess the niche divergence hypothesis (a proxy for natural selection). We found that both species had dimorphic head shapes; male heads (i.e., length, width, and depth) were significantly larger than female heads (P < 0.05, in all cases) in E. grammica, and male heads of E. velox were significantly longer than those of females (P < 0.05). Chi-square test revealed that there were significant differences in the proportion (hymenopteran and orthopteran) and sizes of prey type between the two sexes of E. grammica; conspecific males and females of E. velox differed in the proportion of coleopteran and hymenopteran prey. Both males and females of these two species had a high niche overlap index (range from ~ 0.78–0.99) with each other. There were also significant differences in the sizes of the heads and prey between the two species (P < 0.05). However, the interspecific differences were mainly caused by interspecific male–male differences in morphological and prey traits. In summary, we believe that both natural (pressures from resource competition) and sexual selection drive sexual head shape dimorphism in these two sympatric lizards, owing to high food resource competition in arid regions. Therefore, head trait divergence can reduce competition by resulting in a preference for different prey types.